Nanoparticle: Drug delivery system for cancer therapy - Joseph, Nisha Mary; Sharma, Pramod Kumar (Asian Journal of Pharmaceutics (AJP), 2014)
Nanoparticle has emerged as a promising strategy for the efficient delivery of drugs used in the treatment of cancer by avoiding the reticuloendothelial system, utilizing the enhanced permeability and retention effect and tumor-specific targeting. Delivery methods using nanoparticle are highlighted including both degradable and non-degradable polymers. The preparation techniques include emulsion polymerization, micelle polymerization, desolvation of macromolecule, and emulsion-solvent evaporation methods.The particle size of the polymeric nanoparticle is in the nanometer range (10-1000 nm) and is dependent on the method of preparation employed.